Graves’ Ophthalmopathy: VISA versus EUGOGO Classification, Assessment, and Management - Jesús Barrio-Barrio; Alfonso L. Sabater; Elvira Bonet-Farriol; Álvaro Velázquez-Villoria; Juan C. Galofré (Journal of Ophthalmology)
Graves’ ophthalmopathy (GO) is an autoimmune inflammatory disorder associated with thyroid disease which affects ocular and orbital tissues. GO follows a biphasic course in which an initial active phase of progression is followed by a subsequent partial regression and a static inactive phase. Although the majority of GO patients have a mild, self-limiting, and nonprogressive ocular involvement, about 3–7% of GO patients exhibit a severe sight-threatening form of the disease due to corneal exposure or compressive optic neuropathy. An appropriate assessment of both severity and activity of the disease warrants an adequate treatment. The VISA (vision, inflammation, strabismus, and appearance), and the European Group of Graves’ Orbitopathy (EUGOGO) classifications are the two widely used grading systems conceived to assess the activity and severity of GO and guide the therapeutic decision making. A critical analysis of classification, assessment, and management systems is reported. A simplified “GO activity assessment checklist” for routine clinical practice is proposed. Current treatments are reviewed and management guidelines according to the severity and activity of the disease are provided. New treatment modalities such as specific monoclonal antibodies, TSH-R antagonists, and other immunomodulatory agents show a promising outcome for GO patients.